The Geography of Grammar: Nebrija's Appropriation of the Laus Tradition in the Prologue to the Introduciones latinas (1488). Issue 2 (1st January 2015) - Ekman, Erik
Abstract: This article examines the prologue of Antonio de Nebrija's bilingual Castilian-Latin grammar, the 1488 Introduciones latinas, as a historical document. In this text Nebrija echoes the Laus Hispaniae [praise of Spain] first employed by Isidore of Seville in the History of the Goths, and then by various medieval historians including Rodrigo Ximenez de Rada and Alfonso X, in support of the neo-Gothic myth. Nebrija follows in the tradition of these texts in content and structure, but writes neither in favour of the Goths nor against the Arabs. Rather, he bypasses the Middle Ages to locate the true cultural heritage and borders of Spain in Roman Hispania. Nebrija uses the geography of Iberia to metonymically join the Roman and Latin past to the contemporary vernacular present and thereby close the gap between past and present made evident by his bilingual grammar.